258 NK gene signature in SLE. (April 2019) - Fewings, Nicole L; Swaminathan, Sanjay; Booth, David; Lin, Ming Wei
Abstract : Background: SLE has traditionally been considered a disease of dysregulated B cells and the production of pathogenic autoantibodies. Evidence that other cell types contribute to the observed pathology is being recognised with the advent of a new techniques providing focused avenues of exploration. The aim of this study was to determine which genes are differentially expressed in patients compared to healthy an autoimmune controls. This may then be lead to downstream intracellular signalling pathways and aberrant cytokine production which may contribute to the understanding of the pathogenesis of SLE. Methods: Whole blood RNA was extracted from 46 SLE patients with heterogeneous disease manifestations and at different stages of disease activity, 5 Autoimmune encephalitis and 20 healthy controls. Gene expression was measured using a Nanostring nCounter mRNA expression assay incorporating over 500 immunological genes. Data was analysed using Partek Genomics Suite to identify differentially expressed genes and find pathways that may be of interest to interrogate further in the context of SLE. Results: Gene expression analysis unsurprisingly showed higher expression of interferon-related genes in SLE (MX1, GBP1, IRF7, IFIT2), however we also found that there were genes that were under-expressed. An NK signature with genes such as KLRC2, KLRC1, KLRB1, KLRF1, KLRG1, PRF1 and IL2RB shows the potential value of the approach to discern the important cell types in the development of SLE. Conclusions: The most significantly differentially expressed genes in SLE show an NK signature, with genes that encode activating and inhibitory NK receptors having reduced expression compared to healthy controls. This NK signature recognises a role for this arm of the innate immune response as a unique fingerprint of SLE. Funding Source(s): None